BACHELOR DEGREE IN APPLIED LEGAL STUDIES: SOME QUESTIONS - Alla V. Vereschagina; Oksana O. Martynenko (Высшее образование в России)
The article is devoted to the experiment in introducing an applied bachelor degree program for law students. The authors have formulated the criterions, which, by their opinion, it is necessary toadhere while working out the education standards and curriculum for bachelor’s applied legal studies program. The paper also contains the prognosis on the development of legal education. The result of this experiment will influence it.